Cross-sectional associations between air pollution and chronic bronchitis: an ESCAPE meta-analysis across five cohorts. Issue 11 (11th August 2014) - Cai, Yutong; Schikowski, Tamara; Adam, Martin; Buschka, Anna; Carsin, Anne-Elie; Jacquemin, Benedicte; Marcon, Alessandro; Sanchez, Margaux; Vierkötter, Andrea; Al-Kanaani, Zaina; Beelen, Rob; Birk, Matthias; et al.
Abstract : Background: This study aimed to assess associations of outdoor air pollution on prevalence of chronic bronchitis symptoms in adults in five cohort studies (Asthma-E3N, ECRHS, NSHD, SALIA, SAPALDIA) participating in the European Study of Cohorts for Air Pollution Effects (ESCAPE) project. Methods: Annual average particulate matter (PM10, PM2.5, PMabsorbance, PMcoarse ), NO2, nitrogen oxides (NOx ) and road traffic measures modelled from ESCAPE measurement campaigns 2008–2011 were assigned to home address at most recent assessments (1998–2011). Symptoms examined were chronic bronchitis (cough and phlegm for ≥3 months of the year for ≥2 years), chronic cough (with/without phlegm) and chronic phlegm (with/without cough). Cohort-specific cross-sectional multivariable logistic regression analyses were conducted using common confounder sets (age, sex, smoking, interview season, education), followed by meta-analysis. Results: 15 279 and 10 537 participants respectively were included in the main NO2 and PM analyses at assessments in 1998–2011. Overall, there were no statistically significant associations with any air pollutant or traffic exposure. Sensitivity analyses including in asthmatics only, females only or using back-extrapolated NO2 and PM10 for assessments in 1985–2002 (ECRHS, NSHD, SALIA, SAPALDIA) did not alter conclusions. In never-smokers, all associations were positive, but reached statistical significance only for chronic phlegm with PMcoarse OR 1.31 (1.05 to 1.64) per 5 µg/m 3 increase and PM10 with similar effect size. Sensitivity analyses of older cohorts showed increased risk of chronic cough with PM2.5abs (black carbon) exposures. Conclusions: Results do not show consistent associations between chronic bronchitis symptoms and current traffic-related air pollution in adult European populations.